Risk Management in The Conduct of Tenders and Selection of Construction Services in Klungkung Regency - I Made Kusnaedi; Anak Agung Gde Agung Yana; Anak Agung Diah Parami Dewi (Enrichment: Journal of Multidisciplinary Research and Development, 2026)
The high complexity and uncertainty in the pre-contract stage of construction service procurement through tenders and selection processes create various risks that may cause work delays, cost overruns, decreased quality of construction outcomes, and even state losses. This study aims to identify risk events, analyze risk agents, and formulate preventive mitigation strategies based on the priority of risk agents to support the implementation of risk management and improve government procurement governance. This study used a mixed-methods approach with an exploratory design through literature reviews, in-depth interviews, brainstorming, and surveys of construction service procurement stakeholders in the Klungkung Regency Government. The data were analyzed using the House of Risk (HOR) model, which includes HOR Phase 1 to determine the priority of risk agents and HOR Phase 2 to formulate the most effective mitigation actions. The study identified 30 risk events and 38 risk agents in the pre-contract stage of construction service procurement. The HOR Phase 1 analysis identified 17 priority risk agents, with the primary cause being the limited competence and capacity of the Commitment-Making Officer (Pejabat Pembuat Komitmen; PPK) in preparing procurement preparation documents. HOR Phase 2 identified 37 preventive actions prioritized based on the effectiveness-to-difficulty ratio. The top-priority action was requiring Commitment-Making Officers to participate in procurement competency training and certification. Improving human resource competence, strengthening document review and supervision, developing standards and standard operating procedures (SOPs), and optimizing internal controls were proven effective in minimizing risks and supporting effective, transparent, and accountable construction service procurement.